Significance of Nepal’s Foreign Policy in the Present Strife-torn World - Yadav, Prabhu Ray (NCWA Annual Journal, 2025)
This paper portrays international conflicts and their impact on Nepal, highlighting how Nepal’s foreign policy reflects the exercise of power in such battles. It also analyzes the implications on Nepal’s interests in the present strife-torn world. Nepal has been a permanent supporter of international organizations. The research depicts Nepal’s role in global and domestic disputes. International conflicts, disputes and disparities remain a significant challenge to Nepal’s geopolitical stability. Efforts to maintain peace and stability focus on addressing the root causes and consequences of these conflicts within Nepal’s geopolitical landscape. This study analyzes Nepal’s non-aligned diplomacy considering its location between powerful neighboring countries. It also underscores the importance of peacekeeping missions to promote global peace and harmony. In essence, this paper studies the widespread economic, political, humanitarian and environmental challenges caused by international conflicts, while also investigating how Nepal’s diplomacy tackles the influence of global powers and modern technological advancements in a conflict national and international political environment.